Debating the implications of the urban councils act Chapter 29.15 (1996) on the practice of good corporate governance in Zimbabwe’s urban local authorities - Mutema, Edson P. (Asian Economic and Social Society, 2016)
A publication by Edson Paul Mutema, a Lecturer in the Department of Local Governance, Midlands State University